2019
DOI: 10.1002/jcsm.12427
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise preconditioning and HSP72 on diaphragm muscle function during mechanical ventilation

Abstract: Background Mechanical ventilation (MV) is a life‐saving measure for patients in respiratory failure. However, prolonged MV results in significant diaphragm atrophy and contractile dysfunction, a condition referred to as ventilator‐induced diaphragm dysfunction (VIDD). While there are currently no clinically approved countermeasures to prevent VIDD, increased expression of heat shock protein 72 (HSP72) has been demonstrated to attenuate inactivity‐induced muscle wasting. HSP72 elicits cytoprotectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 58 publications
2
29
0
1
Order By: Relevance
“…showed that exercise increases the expression of heat shock protein 72 (HSP72), which reduces the expression of atrophic transcript factors and oxidative stress. These responses preserve diaphragm muscle function in animals with diaphragm dysfunction . Molecular adaptations in respiratory muscles were out of the scope of our study.…”
Section: Discussionmentioning
confidence: 92%
“…showed that exercise increases the expression of heat shock protein 72 (HSP72), which reduces the expression of atrophic transcript factors and oxidative stress. These responses preserve diaphragm muscle function in animals with diaphragm dysfunction . Molecular adaptations in respiratory muscles were out of the scope of our study.…”
Section: Discussionmentioning
confidence: 92%
“…It is risky to limit the examples of how ACSM colleagues have advanced science and medicine, since other important contributions are easily and unintentionally omitted. Nevertheless, contributions of the following individuals to physiology, and sports medicine should not be overlooked: Jere Mitchell, in cardiovascular physiology and medicine; 186 John Holloszy, in mitochondrial biogenesis; 187 L. Bruce Gladden, in the regulation of intermediary metabolism; 18 , 188 Jim Barnard, V. Reggie Edgerton, and Ken Baldwin, in muscle fiber heterogeneity; 47 , 48 Scott Powers, in redox signaling and preconditioning of the heart to cardiovascular insults; 189 Karl Wasserman and Jerry Dempsey, in pulmonary physiology and medicine; 25 , 190 Tom Fahey, in translating the lessons of physiology and sports medicine to the literature for health care professionals and the lay public; 191 , 192 , 193 and Tim White, in the administration of higher education ( https://www2.calstate.edu/csu-system/chancellor/Pages/meet-the-chancellor.aspx ). In the aggregate, our scientists, clinicians, and staff at the ACSM know well how the body works under stress, in illness, and after injury.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Hsp70/90 are considered mainly intracellular molecular chaperones, which makes them cytoprotective against stressful stimuli. In skeletal muscle cells, overexpression of Hsp70 protects against muscle damage and age-related muscle dysfunction [111] as well as disuse or mechanical ventilation-induced muscle atrophy [112,113,114]. However, under pathological conditions, Hsp70 and Hsp90 can be released into extracellular space where they act as DAMPs [115].…”
Section: Cachectic Cancers Induce Muscle Catabolism By Activatingmentioning
confidence: 99%